Hubungan Manajemen Inovasi dengan Kreativitas Pegawai di Kementerian Agama Kabupaten Purwakarta - Pitri, Silvi Amelia; Badrudin, Badrudin; Kasmin, Kasmin (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine the relationship between innovation management and employee creativity. This research was conducted at the Ministry of Religion of Purwakarta Regency. This study uses a quantitative descriptive approach with correlation types. The results of the study show that: (1) Innovation Management at the Ministry of Religion of Purwakarta Regency, is included in the medium category, which is equal to 3.46 from the results of data processing of 39 respondents; (2) Employee Creativity at the Ministry of Religion of Purwakarta Regency, is included in the medium category, which is equal to 3.39 from the results of data processing of 39 respondents; (3) Based on the results of calculating the correlation between variable X and variable Y, a correlation coefficient of 0.874 is obtained, including a coefficient category of 0.76 – 0.99, meaning that there is a large or very strong relationship. So it can be concluded that there is a relationship between innovation management and employee creativity at the Ministry of Religion of Purwakarta Regency. The results of the calculation of the correlation test show that the significance of innovation management with employee creativity is 0.000 <0.05. The results of the calculation of the correlation test are positive, which means that if innovation management is increased, employee creativity will also increase. Then from the results of the determination coefficient test (R square) of 0.792, which means that the innovation management variable with employee creativity has a contribution of 79.2%. Keywords: Management, Innovation, Creativity, Employees.